Prior Coronary Artery Bypass Graft Surgery and Outcome After Percutaneous Coronary Intervention: An Observational Study From the Pan‐London Percutaneous Coronary Intervention Registry. Issue 12 (16th June 2020) - Rathod, Krishnaraj S.; Beirne, Anne‐Marie; Bogle, Richard; Firoozi, Sam; Lim, Pitt; Hill, Jonathan; Dalby, Miles C.; Jain, Ajay K.; Malik, Iqbal S.; Mathur, Anthony; Kalra, Sundeep Singh; DeSilva, Ranil; et al.
Abstract : Background: Limited information exists regarding procedural success and clinical outcomes in patients with previous coronary artery bypass grafting (CABG) undergoing percutaneous coronary intervention (PCI). We sought to compare outcomes in patients undergoing PCI with or without CABG. Methods and Results: This was an observational cohort study of 123 780 consecutive PCI procedures from the Pan‐London (UK) PCI registry from 2005 to 2015. The primary end point was all‐cause mortality at a median follow‐up of 3.0 years (interquartile range, 1.2–4.6 years). A total of 12 641(10.2%) patients had a history of previous CABG, of whom 29.3% (n=3703) underwent PCI to native vessels and 70.7% (n=8938) to bypass grafts. There were significant differences in the demographic, clinical, and procedural characteristics of these groups. The risk of mortality during follow‐up was significantly higher in patients with prior CABG (23.2%; P =0.0005) compared with patients with no prior CABG (12.1%) and was seen for patients who underwent either native vessel (20.1%) or bypass graft PCI (24.2%; P <0.0001). However, after adjustment for baseline characteristics, there was no significant difference in outcomes seen between the groups when PCI was performed in native vessels in patients with previous CABG (hazard ratio [HR], 1.02; 95%CI, 0.77–1.34; P =0.89), but a significantly higher mortality was seen among patients with PCI to bypass grafts (HR, 1.33; 95% CI, 1.03–1.71; P =0.026). This was seen after multivariate adjustment and propensity matching. Conclusions: Patients with prior CABG were older with greater comorbidities and more complex procedural characteristics, but after adjustment for these differences, the clinical outcomes were similar to the patients undergoing PCI without prior CABG. In these patients, native‐vessel PCI was associated with better outcomes compared with the treatment of vein grafts.